About Nikolay Kolyada (Филологический класс, 2015)
The article presents a transcript of a talk with N. L. Leiderman about N. Kolyada, recorded in February 2010. The author speaks in detail about his meetings with the dramatist, about the history of writing his monograph «Dramatic Works of Nikolay Kolyada» and provides an analysis of the dramatist‘s creative legacy. N. L. Leiderman also dwells on the reasons of popularity of N. Kolyada both in Russia and in the West. The author touches upon the modern state of the Kolyada Theatre and the role of the dramatist in the creation of the Urals dramatic school.